2016
DOI: 10.1186/s12906-016-1140-y
|View full text |Cite
|
Sign up to set email alerts
|

Antiosteoporotic effect of Petroselinum crispum, Ocimum basilicum and Cichorium intybus L. in glucocorticoid-induced osteoporosis in rats

Abstract: BackgroundGlucocorticoid-induced osteoporosis (GIO) is one of the serious side effects which have become the most common secondary osteoporosis. The purpose of this study is to evaluate the effect of aqueous extract of parsley, basil and chicory on glucocorticoid-induced osteoporosis in rats.MethodsFifty Female rats were divided into five groups and treated for 8 weeks as follow: group 1 served as control; group (2) subcutaneously injected with 0.1 mg/kg b. wt. dexamethasone dissolved in saline; group 3 receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 41 publications
10
42
0
1
Order By: Relevance
“…The ethyl acetate fraction proved to have a positive fl avonoid and essential oil content (terpenoid) based on phytochemical screening results performed on the ethyl acetate fraction. According to (21) , Ocimum basilicum contains flavonoids such as luteo.6-arabinose.8-glucose, luteo.6-glucose.8arabinose, apig.6-rhaminose.8-galactose, apig.6rhaminose.8-glucose, apig.6-glucose.8-rhaminose, routine, hespiridin, rosmarinic acid, apig.7-oneohespiroside, apiginine-7-glucose, quercitin, naringenin, hespirtin, campferol, apigenin. Naringenin has antidepressant activity through the serotonergic and noradrenergic system (18) .…”
Section: Resultsmentioning
confidence: 99%
“…The ethyl acetate fraction proved to have a positive fl avonoid and essential oil content (terpenoid) based on phytochemical screening results performed on the ethyl acetate fraction. According to (21) , Ocimum basilicum contains flavonoids such as luteo.6-arabinose.8-glucose, luteo.6-glucose.8arabinose, apig.6-rhaminose.8-galactose, apig.6rhaminose.8-glucose, apig.6-glucose.8-rhaminose, routine, hespiridin, rosmarinic acid, apig.7-oneohespiroside, apiginine-7-glucose, quercitin, naringenin, hespirtin, campferol, apigenin. Naringenin has antidepressant activity through the serotonergic and noradrenergic system (18) .…”
Section: Resultsmentioning
confidence: 99%
“…The dose of dexamethasone 0.1 mg/kg subcutaneous (toxic drug) was used in the present study as reported from Hozayen et al, 2016 [27].…”
Section: Selection Of Dose and Osteoporosis Inductionmentioning
confidence: 99%
“…Animal dose (mg/kg) = Human dose (mg/kg) * Human Km [28]/ Animal Km Where, Km = body weight (kg) divided by BSA (m2) Human Km = 37 Animal Km (rat) = 6 Induction of osteoporosis was done by using dexamethasone 0.1 mg/kg s.c for three times per week for 8 consecutive weeks and treatment with drugs continued up to 12 weeks as per the treatment schedule between 10 and 12 a.m. [27].…”
Section: Selection Of Dose and Osteoporosis Inductionmentioning
confidence: 99%
“…Recently, some cytokines have been found to participate in bone metabolism by interacting with OB or OC (Almeida et al., ; Fahmy & Soliman, ; Frankel, Seshadri, McDowall, & Cornish, ; Gimeno, Zaragozá, Vivó‐Sese, Viña, & Miralles, ; Hough et al., ; Johansson & Melhus, ; Kindmark, Melhus, Ljunghall, & Ljunggren, ; Oršolić et al., ) such as vascular endothelial growth factor (VEGF), osteoprotegerin (OPG), transforming growth factor (TGF‐β), interleukin (IL‐1), and granulocyte‐macrophage colony‐stimulating factor (GMCSF). The effects of estrogen on these cytokines have been widely reported (Hozayen, El‐Desouky, Soliman, Ahmed, & Khaliefa, ; Iolascon et al., ; Kneissel, Studer, Cortesi, & Susa, ; Liao et al., ; Muthusami et al., ; Zafar, Weaver, Zhao, Martin, & Wastney, ). However, there are few studies about the effects and mechanisms of soybean isoflavone on these cytokines.…”
Section: Introductionmentioning
confidence: 99%